(Epi)genetic Inheritance in Schistosoma mansoni: A Systems Approach. Issue 4 (April 2017) - Cosseau, Céline; Wolkenhauer, Olaf; Padalino, Gilda; Geyer, Kathrin K.; Hoffmann, Karl F.; Grunau, Christoph
Abstract : The G × E concept, in which genotype × environment interactions bring about the phenotype, is widely used to describe biological phenomena. We propose to extend the initial notion of the concept, replacing G by 'inheritance system'. This system, comprised of both genome and epigenome components, collectively interacts with the environment to shape the development of a phenotype. In the case of the human blood fluke Schistosoma mansoni, responsible for intestinal bilharzia, the phenotypic trait that is most relevant to global health is infection success. Taking a systems biology view we show how genetic and epigenetic interactions result in ephemeral, but also heritable, phenotypic variations that are important for infection success. Trends: There is an intense debate about the importance of nongenetic inheritance for evolution. Schistosoma mansoni epigenotype components are important players in parasite development and host interactions. We use S. mansoni as an example to introduce the notion of 'inheritance system' in which genotype and the epigenotype components collectively interact with the environment to shape the development of a phenotype.